2014
DOI: 10.1007/s00277-014-2149-2
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide in relapsed and refractory multiple myeloma disease: feasibility and benefits of long-term treatment

Abstract: Lenalidomide in combination with dexamethasone is an effective and well-established treatment of relapsed or refractory multiple myeloma (rrMM) disease. Due to the scarcity of reports assessing benefit and risk of long-term lenalidomide treatment in non-selected rrMM patients, we retrospectively analysed the long-term outcome in patients with rrMM treated with lenalidomide and dexamethasone. Sixty-seven patients (pts) who were treated with lenalidomide/dexamethasone for rrMM in the approved indication from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…These were based on subgroup analyses of large prospective trials in which treatment was given until progression or, alternatively, on small single-institution experiences. [8][9][10][11][12] In 1 study of 50 patients, those treated for > 3 years had a longer median TTP compared with those treated for 2 to 3 years, regardless of the response rate. 10 In another small retrospective study of 67 patients, OS and the overall response rate were significantly better for patients treated with lenalidomide and dexamethasone for > 12 months compared with patients who stopped treatment at < 12 months for reasons other than progression.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…These were based on subgroup analyses of large prospective trials in which treatment was given until progression or, alternatively, on small single-institution experiences. [8][9][10][11][12] In 1 study of 50 patients, those treated for > 3 years had a longer median TTP compared with those treated for 2 to 3 years, regardless of the response rate. 10 In another small retrospective study of 67 patients, OS and the overall response rate were significantly better for patients treated with lenalidomide and dexamethasone for > 12 months compared with patients who stopped treatment at < 12 months for reasons other than progression.…”
Section: Introductionmentioning
confidence: 98%
“…10 In another small retrospective study of 67 patients, OS and the overall response rate were significantly better for patients treated with lenalidomide and dexamethasone for > 12 months compared with patients who stopped treatment at < 12 months for reasons other than progression. 11 However, these studies varied in the extent to which they controlled for patient and disease factors and treatment exposure at baseline and over time-all aspects that can affect OS. Some analyses did not account for selection 8 and/ or survival 10,12 bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above mentioned model was on the borderline of statistical significance, however the fact that the number of LEN cycles was a parameter with the strongest impact on treatment response achievement (p = 0.026919) pays attention. In studies by Zago and Mele, LEN + DEX treatment used over 12 months significantly increased ORR [7,15]. Moreover, Harousseau revealed that LEN + DEX treatment continuation increased best response rate [16].…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, similarly to treatment response achievement analysis, the number of LEN treatment cycles was a substantial OS-determining factor. In studies by Zago, OS in patients receiving treatment >12 and <12 months was 43 months and 20 months, respectively; and the obtained difference was statistically significant [15]. In addition to the number of previous lines of treatment and disease stage according to DurieSalmon staging system, San Miguel demonstrated that ␤-2 -M levels and LEN + DEX treatment cycles had important impact on patients' survival time [19].…”
Section: Discussionmentioning
confidence: 95%